2010
DOI: 10.5625/lar.2010.26.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity ofSanguisorba officinalisagainstHelicobacter pylori

Abstract: In this study, a medicinal herbal plant, Sanguisorba officinalis, was examined and screened for anti-Helicobacter pylori (H. pylori) activity. Seventy percent ethanol was used for herbal extraction. For anti-H. pylori activity screening, inhibitory zone tests as an in vitro assay and in vivo study using a Mongolian gerbil (Meriones unguiculatus) model were performed. Also, the safety of herbal compounds was evaluated by animal study. As a result of inhibitory zone test, Sanguisorba officinalis extract demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…It is unclear whether the anti- P. acnes compounds are rich in the roots but not in the aerial parts of S. officinalis L. Among the extracts and their respective EA fractions, the SOR ME and ME-EA showed the lowest MIC and MBC values against P. acnes . Furthermore, the SOR ME and ME-EA showed antimicrobial activity against numerous Gram-negative and -positive bacteria, which corresponds to earlier works [ 31 , 37 , 38 ]. It suggested that the SOR ME displayed a broad spectrum of antibacterial activity, whereas both the CWE and HWE displayed a narrow spectrum of antibacterial activity.…”
Section: Discussionsupporting
confidence: 90%
“…It is unclear whether the anti- P. acnes compounds are rich in the roots but not in the aerial parts of S. officinalis L. Among the extracts and their respective EA fractions, the SOR ME and ME-EA showed the lowest MIC and MBC values against P. acnes . Furthermore, the SOR ME and ME-EA showed antimicrobial activity against numerous Gram-negative and -positive bacteria, which corresponds to earlier works [ 31 , 37 , 38 ]. It suggested that the SOR ME displayed a broad spectrum of antibacterial activity, whereas both the CWE and HWE displayed a narrow spectrum of antibacterial activity.…”
Section: Discussionsupporting
confidence: 90%
“…For centuries, traditional Chinese medicine has been widely used in East Asia to treat diseases [6][7][8][9]. Notably, Diyv Shengbai Tablet, whose main component is the powder of Sanguisorba officinalis L., has been generally used to treat leukopenia in clinical practice [10][11][12][13][14]. Sanguisorba officinalis L. (the dried root of Sanguisorba, Rosaceae) is a traditional medicinal herb that is widely distributed in Europe and Asia.…”
Section: Introductionmentioning
confidence: 99%
“…For centuries, traditional Chinese medicine has been widely used in East Asia to treat diseases [6–9]. Notably, Diyv Shengbai Tablet, whose main component is the powder of Sanguisorba officinalis L., has been generally used to treat leukopenia in clinical practice [10–14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Chinese pharmacopoeia, it plays a major role in the treatment of hematochezia, bleeding hemorrhoids, bloody flux, metrorrhagia and metrostaxis, bleeding wounds, burns and scalds, and swollen carbuncles [ 3 ]. Besides, in vivo and in vitro studies have illustrated that plants from the S. officinalis present a wide range of pharmacological properties, including hemostatic, antioxidant [ 4 ], anti-inflammatory [ 5 ], antiviral [ 6 ], antibacterial [ 7 , 8 ], anti-tumor [ 9 ], neuroprotective and hypoglycemic activities [ 10 ]. Simultaneously, in Chinese medical practice, many drugs (e.g., tablets and powders) that contain S. officinalis roots have been applied to treat leukopenia, hemorrhaging and burns [ 11 ].…”
Section: Introductionmentioning
confidence: 99%